Multicultural Awareness in EFL Classrooms in Indonesia: Enhancing Communicative Competence and Empathy - ST. Marhana Rullu; Ribut Wahyu Eriyanti; Joko Widodo; Masduki (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Indonesia's linguistic and cultural diversity creates both opportunities and challenges for English as a Foreign Language (EFL) instruction, yet multicultural awareness is often sidelined in favor of purely linguistic accuracy. This study aims to addres how multicultural awareness is represented and operationalized in EFL teaching and how it contributes to students’ communicative competence and intercultural empathy. A qualitative meta-summary was conducted using ten Scopus-indexed studies published between 2020 and 2025, focusing on Indonesian EFL contexts. The study identifies three main aspects: integrating local culture, developing context-based skills, and fostering empathy. The findings conclude that effective EFL teaching goes beyond language accuracy, requiring cultural and emotional relevance. This research provides a significant academic contribution by offering a synthesized framework for culturally responsive pedagogy, emphasizing that teacher agency and institutional support are the primary catalysts for developing globally competent yet locally rooted learners.